2021
DOI: 10.3389/fnbeh.2021.663761
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonic Type Behavior and Anxiety Profile of Wistar-UIS Rats Subjected to Chronic Social Isolation

Abstract: Chronic Social Isolation (CSI) is a model of prolonged stress employed in a variety of studies to induce depression and anxious behavior in rats. The present study aims to evaluate the effect of CSI on male Wistar rats in terms of “anhedonic-type” behavior in the Sucrose Preference Test (SPT) and anxiogenic profile in the elevated-plus-maze (EPM) test, as well as evaluating the effect of resocialization upon sucrose consumption. A total of 24 adolescent male Wistar rats were evaluated. The animals were housed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The animals submitted to SI showed emotional dysregulation in the Sucrose Preference Test (Brenes & Fornaguera, 2008; Yildirim et al, 2012). Sucrose intake was higher in SI animals, which indicates a change in the reward threshold because of the greater need to experience rewarding sensations (Acero‐Castillo et al, 2021; Brenes et al, 2020). Alternatively, Yildirim et al (2012) observed higher sucrose consumption in SI and EE animals, indicating that the stress caused by other behavioral tests directly affected the result in animals submitted to EE.…”
Section: Discussionmentioning
confidence: 99%
“…The animals submitted to SI showed emotional dysregulation in the Sucrose Preference Test (Brenes & Fornaguera, 2008; Yildirim et al, 2012). Sucrose intake was higher in SI animals, which indicates a change in the reward threshold because of the greater need to experience rewarding sensations (Acero‐Castillo et al, 2021; Brenes et al, 2020). Alternatively, Yildirim et al (2012) observed higher sucrose consumption in SI and EE animals, indicating that the stress caused by other behavioral tests directly affected the result in animals submitted to EE.…”
Section: Discussionmentioning
confidence: 99%
“…EPM is a widely used rodent model for evaluating anxietyrelated behavior, based on the natural preference of these animals for dark and protected places. Anxiety is measured by the proportion of test time spent in the closed arms of the maze, without coming into contact with the open areas (Acero-Castillo et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Anhedonia, in this context, can be defined as low reward sensitivity (Rygula et al 2005). It should be noted that the concentration of sucrose solutions used can strongly affect the level of its ingestion (Acero-Castillo et al 2021;Markov 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Rats' animal experimentation model is based on the preference nature of water with sucrose dissolved in it over regular water [16] , [17] . Wherein the preference pattern of sucrose solutions concentrations at 1% [18] . When a rodent shows a lack of interest in the sucrose solution, it is said to be exhibiting anhedonia which is a classic component of depressive disorders [19] .…”
Section: Methodsmentioning
confidence: 99%